Shape Recognition Elicited by Microsecond Flashes is Not Based on Photon Quantity. (April 2014) - Greene, Ernest
It is generally thought that the perceptual impact of a brief flash of light is determined by the quantity of photons the flash delivers. This means that only the total quantity of photons is important below a critical duration of about 30–100 ms. Recent findings have challenged this concept and the present work provides additional evidence that it is not correct. The first experiment reported here delivered a given quantity of photons in under 200 μs, either as a single threshold-intensity flash or as multiple flashes at the same intensity. The single flash was ineffective at eliciting recognition, but multiple flashes became progressively more effective as the number of flashes was increased. A second experiment varied the number of 10 μs flashes. The effectiveness of multiple flashes was far higher than would be expected on the basis of the total quantity of photons being delivered. The results of both experiments suggest that the brief transitions of intensity provided by the flashes are far more important than the quantity of photons. A final experiment examined the combined impact from two threshold-intensity flashes as the interstimulus interval was increased. The pair members were able to combine their influence for at least 100 ms. These results call for more attention to how very brief light flashes generate signals that convey image content.